Post hysterectomy fallopian tube prolapse: a rare case - S., Priya; C., Sarojamma; P. A., Sailakshmi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Fallopian tube prolapse into the vaginal vault is a very complication of hysterectomy where the adnexa is preserved. The overall occurrence after all routes of hysterectomy is 0.01-0.05%. Several factors have been suggested to contribute to the condition such as vault hematoma, improper closure of vault, early resumption of sexual activity. Due to the misdiagnosis, there is often delay in the diagnosis and its management. The only means of definitive diagnosis is histopathology. A 30-year-old P2l2 presented to us after 3 years of post-hysterectomy with abdominal pain and bleeding pv on and off. On examination prolapsed fallopian tube was found in the vaginal vault on speculum. Biopsy was done in the outside hospital and was confirmed to be the tube. Patient underwent combined laparoscopic and vaginal method. Vaginal excision of the tube was done. Prevention by prophylactic salpingectomy and by suturing the adnexa high up in the pelvis in abdominal hysterectomy.